A pharmacy carer support service: obtaining new insight into carers in the community. (6th May 2018) - McMillan, Sara S; King, Michelle A; Stapleton, Helen; Sav, Adem; Kelly, Fiona; Wheeler, Amanda J
Abstract: Objectives: Unpaid carers have many and varied responsibilities in society, which can include medication management for the person they support. However, the potential for Australian community pharmacies to better assist carers is relatively unexplored. This mixed-methods study investigated the acceptability of a local carer support service by trained community pharmacy staff, including issues regarding the implementation and impact of this service. Methods: Staff from 11 community pharmacies in South East Queensland, Australia, were trained to deliver a six-step carer support service between September 2016 and March 2017. Pharmacies were supported by a carer and pharmacist mentor pair and asked to recruit up to six carers each. Evaluations of staff training were descriptively analysed. Semi-structured interviews were undertaken with pharmacy staff, and interview transcripts were analysed thematically. Key findings: Staff training evaluations were positive; participants acquired new information about carers and rated the service highly in terms of its importance within the pharmacy setting. Feedback was obtained on how to improve the training, such as further opportunities for role-play. Seven staff members were interviewed, and data analysis revealed two main themes: (1) implementation of the carer support service and (2) perceived impact on pharmacy staff. Positive attitudes towards recognising and supporting carers, and training and mentoring were identified with community pharmacies viewed as a suitable place for delivering this new service. New insights into the impact of caring were widely reported, which staff had not appreciated from previous carer interactions. Structural issues, including space and time pressures, and a lack of awareness about the types of support currently available to carers were emphasised. Conclusion: Pharmacy staff are well positioned to support carers. Engaging carers in conversation to better understand their needs is a small step with potential for big gains, including a more empathetic understanding of their individual circumstances and overall well-being.